2021
DOI: 10.3390/diagnostics11091648
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of ADAMTS-13 and von Willebrand Factor in COVID-19 Patients: Prospective Evaluation by Care Setting

Abstract: Background: Endothelial dysfunction, coupled with inflammation, induces thrombo-inflammation. In COVID-19, this process is believed to be associated with clinical severity. Von Willebrand factor (VWF), and a disintegrin and metalloproteinase with thrombospondin motifs 13 (ADAMTS-13), are strong markers of endothelial dysfunction. We evaluated the impact of the VWF/ADAMTS-13 fraction on COVID-19 severity and prognosis. Materials and methods: A cohort study including 74 COVID-19 patients, with 22 admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To calculate these ratios, the ADAMTS-13 concentration and vWF activity were measured in IU/mL (%/100). The literature contains data on the prognostic value of these ratios in terms of the severity of infection [ 13 ]. For example, a vWF:RCo/ADAMTS-13:activity level > 5.7 is associated with ICU admission, and a level > 6.5 was associated with increased patient mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate these ratios, the ADAMTS-13 concentration and vWF activity were measured in IU/mL (%/100). The literature contains data on the prognostic value of these ratios in terms of the severity of infection [ 13 ]. For example, a vWF:RCo/ADAMTS-13:activity level > 5.7 is associated with ICU admission, and a level > 6.5 was associated with increased patient mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic and prognostic value of vWF/ADAMTS-13 ratio has been studied in several studies [ 12 , 13 ]. In our study we found that, at the time of patient’s admission to a hospital, the vWF:RCo/ADAMTS-13:activity ratio has a greater diagnostic value than the vWF/ADAMTS-13 ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of hospitalized patients with a suspected heparin-induced thrombocytopenia (HIT), high levels of plasma VWF antigen and low levels of ADAMTS13 activity were associated with increased mortality regardless of the HIT testing results by immunoassay or serotonin-releasing assay [76]. The prognostic value of the VWF/ADAMTS13 ratios in COVID-19 patients has also been reported by other groups [67,77]. Interestingly, plasma ADAMTS13 activity alone is not an independent predictor of all in-hospital mortality of COVID-19 patients after adjusting for other related factors in our study (not shown).…”
Section: Discussionmentioning
confidence: 59%
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%